Escala de conducta prosocial (EP): estructura interna e invarianza factorial en adultos peruanos - Ramirez-Sanchez, Erika (2025)
This study analyzed the psychometric properties of the Prosocial Behavior Scale (PB). A total of 448 Peruvian adults participated, 323 (72.1%) women and 125 (27.9%) men, aged between 18 and 65 years (M = 25.13, SD = 7.03). The metric quality of the 16 items was examined. Using confirmatory factor analysis, 10 models were compared, with the best fit found for the bifactor model, consisting of two specific factors and one general factor: χ²/df = 3.155, CFI = .973, TLI = .963, RMSEA [90% CI] = .069 [.060; .079], SRMR = .039, and WRMR = 0.917, with specific indices ωH > .80, ECV < .60, and PUC < .80. Internal consistency reliability was confirmed (ꞷ = .945). Measurement invariance was evaluated through multigroup confirmatory factor analysis, showing that the scale is invariant across gender and age groups: ΔCFI ≤ .010, ΔRMSEA ≤ .015, and ΔSRMR ≤ .030.In conclusion, the PB Scale demonstrates solid psychometric evidence for use with Peruvian adults.